ANALISIS KANDUNGAN MINERAL (KALSIUM, KALIUM,FOSFOR) PADA KULIT PISANG KEPOK DAN PISANG AMBONDENGAN METODE MPAES - Mauli, Mauli Handa Yani; Nofita; Husein, Saddam (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2025)
Banana is one of the most abundant horticultural commodities in Indonesia. Apart from the fruit, banana peels have great potential to be utilized because they contain various minerals that are beneficial to the body, such as calcium, potassium, and phosphorus. However, the utilization of banana peels is still very low because they are often considered as waste. This study aims to analyze the mineral content of kepok and ambon banana peels using the Microwave Plasma Atomic Emission Spectroscopy (MPAES) method. The study was conducted qualitatively and quantitatively. Qualitative analysis involved flame test and precipitation reaction to detect the presence of minerals, while quantitative analysis used MPAES instrument to measure mineral content. Qualitative results showed that kepok and ambon banana peels contained calcium, potassium and phosphorus. Quantitatively, kepok banana peels have an average calcium content of 2,568.7 mg/kg, potassium 5,237.6 mg/kg, and phosphorus 429.13 mg/kg. Ambon banana peel contains an average of 2,095.3 mg/kg calcium, 4,216.3 mg/kg potassium, and 177.43 mg/kg phosphorus. Differences in mineral content were analyzed using Paired sample T-Test and Wilxocon which showed significant differences in calcium and phosphorus levels between the two types of banana peels, while potassium levels showed no significant differences. The results of this study indicate the potential of banana peels as a source of minerals for nutritional supplements and pharmaceutical products. Utilization of banana peels can support organic waste management and increase the added value of banana production.